Stop invasion! The electoral tipping point in anti-immigrant voting - Massimo Bordignon; Matteo Gamalerio; Edoardo Slerca; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
Why do anti-immigrant political parties have more success in areas that host fewer immigrants? Using regression discontinuity design, structural breaks search methods and data from a sample of Italian municipalities, we show that the relationship between the vote shares of anti-immigrant parties and the share of immigrants follows a U-shaped curve, which exhibits a tipping-like behavior around a share of immigrants equal to 3.35%. We estimate that the vote share of the main Italian anti-immigrant party (Lega Nord) is approximately 6% points higher for municipalities below the threshold. Using data on local labor market characteristics and on the incomes of natives and immigrants, we provide evidence which points at the competition in the local labor market between natives and immigrants as the more plausible explanation for the electoral success of anti-immigrant parties in areas with low shares of immigrants. Alternative stories find less support in the data.
Keywords: 330; Ethnische Diskriminierung; Migranten; Politische Einstellung; Wahlverhalten; Kommunalwahl; Italien